2018
DOI: 10.3390/molecules23112917
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genome Sequence of Malus hupehensis: Genome Structure, Comparative Analysis, and Phylogenetic Relationships

Abstract: Malus hupehensis belongs to the Malus genus (Rosaceae) and is an indigenous wild crabapple of China. This species has received more and more attention, due to its important medicinal, and excellent ornamental and economical, values. In this study, the whole chloroplast (cp) genome of Malus hupehensis, using a Hiseq X Ten sequencing platform, is reported. The M. hupehensis cp genome is 160,065 bp in size, containing a large single copy region (LSC) of 88,166 bp and a small single copy region (SSC) of 19,193 bp,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 79 publications
(79 reference statements)
6
14
1
Order By: Relevance
“…Therefore, it is yet to be ascertained whether the conserved SSR motifs found in the four Rubus species of subgenus Anoplobatus and Idaeobatus in this study can also be found in other major lineages of Rubus , such as subgenus Malachobatus and Rubus . The locations of SSR motifs and A/T abundance found in R. boninensis , R. trifidus , and R. crataegifolius (Figure 2B) were consistent with other members of Rosaceae [39,44,45,46,47]. As the utility of cpSSRs has been proven to be valuable in various plant lineages (e.g., Glycine , [48]; Pinus , [49]; Triticum , [50]; Abies , [51]; Cucumis , [52]), we believe that the cpSSR markers developed in this study can be useful for complex studies at both the population and specific level of members of subgenus Anoplobatus and Idaeobatus .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Therefore, it is yet to be ascertained whether the conserved SSR motifs found in the four Rubus species of subgenus Anoplobatus and Idaeobatus in this study can also be found in other major lineages of Rubus , such as subgenus Malachobatus and Rubus . The locations of SSR motifs and A/T abundance found in R. boninensis , R. trifidus , and R. crataegifolius (Figure 2B) were consistent with other members of Rosaceae [39,44,45,46,47]. As the utility of cpSSRs has been proven to be valuable in various plant lineages (e.g., Glycine , [48]; Pinus , [49]; Triticum , [50]; Abies , [51]; Cucumis , [52]), we believe that the cpSSR markers developed in this study can be useful for complex studies at both the population and specific level of members of subgenus Anoplobatus and Idaeobatus .…”
Section: Resultssupporting
confidence: 80%
“…spontanea (11.8%; n = 10). Also, the highest proportions of mononucleotides motifs were found in nine species of Malus chloroplast genomes, with the total number of chloroplast SSR (cpSSRs) ranging from 94 to 101 [46]. Therefore, it is yet to be ascertained whether the conserved SSR motifs found in the four Rubus species of subgenus Anoplobatus and Idaeobatus in this study can also be found in other major lineages of Rubus , such as subgenus Malachobatus and Rubus .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…A highly variable region or hotspot region in the whole chloroplast genome scale can help elucidate the phylogenetic relationships and complex evolutionary history of Rubus as a maternally inherited marker. Recently, several hot spot regions including genic and non-coding regions across the entire plastome were reported in several members of Rosaceae, such as Malus 56 , Prunus 57 , Pyrus 27 , and Rosa 30 . In our current study, we also detected four highly variable regions, including rps16 / trnQ ( Pi = 0.0518) and petA / psbJ ( Pi = 0.0466), as two of the most variable hotspots within the eight Taiwan Rubus endemics, with an average nucleotide diversity ( Pi ) value of 0.01.…”
Section: Discussionmentioning
confidence: 99%
“…All nine species of the genus Artemisia showed similarity in terms of the gene content, intron content, and composition of GC content. The chloroplast genome of angiosperms is highly conserved and several previous studies have also reported high similarity in chloroplast genome sequences of the same lineage [26,31,32,33,34,35]. However, some studies have reported variation in gene numbers and gain or loss of introns at a genus level, as well as at a family level [36,37,38].…”
Section: Discussionmentioning
confidence: 99%